Factors that contribute to job stress and stress level among employees in private institution in Malaysia / Nur Arina Zainudin - Zainudin, Nur Arina (Faculty of Business and Management, 2016)
There are at least hundreds of private institutions in Malaysia. In order to stay on top of the competition and compete with others, the organization need keep all their employees motivated to work in order to produce good quality of productivity. But more or less, stress can be a disturbing factor that may influence employees’ motivation to work. Employees in different organization have different factor that contribute to stress and they face different level of job stress. As for Human Resource Department (HRD), the department itself is the most vital department that keep the entire workforce working together in harmony. UNIKL have several campus around Malaysia and have at least three campus in Kuala Lumpur. Even though this study only focus on one of UNIKL branch campus UniKL Business School (UBIS), still different individual (employee) face different factor of job stress. The first research objective of this study is to identify the factors that contribute to job stress in private institution. Second objective is to measure the employee’s stress level in private institution. Last but not least, the third objective is to examine the relationship between factors of job stress and employee’s stress level in private institution. The respondents total was 50. The data were collected through distribution of questionnaire and interpreted into readable and informative data through Reliability Analysis, Descriptive Analysis and Pearson’s Correlation. The findings support all the objectives listed by the researcher which mean there is significant relationship between all three independent variables which are organization factor, environment factor and personal factor with dependent variable, employee’s stress level at private institution. From the findings, it was found that environment is the most dominant factor that contribute to employee’s level of stress.